(untitled) (Journal of Medical & Health Sciences Review, 2025)
Gut microbiota, a dynamic network of trillions of microbes, choreographs a pervasive impact on innate immune education, preparing the host to fight opportunistic bacterial pathogens like Clostridioides difficile, Pseudomonas aeruginosa, and Klebsiella pneumoniae. This review discusses the mechanisms by which microbial metabolites, such as short-chain fatty acids and secondary bile acids, and dynamic microbial community interactions reeducate innate immune cells like macrophages and nutrophil to maximize pathogen elimination. By epigenetic changes, metabolic reprogramming, and pattern recognition receptor signaling, the microbiota enhances systemic immunity providing a strong defense in immunocompromised conditions. We explore how dysbiosis interferes with such immune training, increasing infection susceptibility, and discuss novel therapy approaches, including probiotics, probiotics and fecal microbiota transplantation, to reestablish immune resilience. Through the integration of state-of-the-art knowledge and the identification of key gaps in research, this review sheds light on the revolutionizing potential of microbiota-targeting interventions towards the mitigation of the emerging danger posed by antimicrobial-resistant infections. Person-centric microbiota-guided treatments are potential game-changers for infection control that can bring down the global burden of opportunistic bacterial disease and the possibility of new immunotherapies in clinical medicine.